Natural resources and violent conflict: Options and actions - Bannon, I (World Bank, 2003)
Eight papers, commissioned under the Governance of Natural Resources Project, present approaches and suggestions for international action to help developing countries better manage their resource wealth and turn this wealth into a driver of development rather than of conflict. Papers discuss including measures relating to the global development agenda and measures relating to the global governance of natural resources and its link to conflict (Ian Bannon and Paul Collier); the natural resource curse (Michael Ross); reporting resource revenues (Philip Swanson, Mai Oldgard, and Leiv Lunde); commodity tracking systems (Corene Crossin, Gavin Hayman, and Simon Taylor); the finance of illicit resource extraction (Jonathan M. Winer and Trifin J. Roule); international instruments of enforcement relating to the trade of conflict resources (Philippe Le Billon); what special risk factors petroleum and mining companies take into account when considering an investment in a zone of actual or potential conflict and what can be done to encourage reputable companies to invest in regions affected by conflict (John Bray); and how the international community might dampen the price shocks affecting developing countries (Patrick Guillaumont and Sylviane Guillaumont Jeanneney). Bannon is with the Conflict Prevention and Reconstruction Unit in the Social Development Department of the World Bank. Collier is with the Center for the Study of African Economics at the University of Oxford and with the Africa Region of the World Bank. Index.